The effects of CLIL on L1 competence development in monolingual contexts. Issue 1 (2nd January 2020) - Navarro-Pablo, Macarena; López Gándara, Yiyi
ABSTRACT: Very little research has been conducted on the effects of CLIL on L1 competence development. This article compares CLIL and non-CLIL learners' levels of attainment in Spanish Language and Literature in seven public schools in the South of Spain. Learners' verbal intelligence and motivation were previously matched in order to homogenise the sample. This study focuses on a total of seven public schools ( N  = 271) in the province of Seville, at both primary and secondary level. Students' performance in L1 (Spanish) was compared to check differences between CLIL and non-CLIL strands. The results suggest that students in CLIL programmes do better in their end-of-year Spanish Language and Literature assessment, compared with students in non-CLIL strands, and that these differences are not due to setting (rural vs. urban). There is also some evidence to suggest that amount, distribution and type of L1 and FL input in CLIL classes might be factors accounting for CLIL learners' positive results in the L1. Teachers and students surveyed generally believe that CLIL has a positive impact in this area, particularly on students' understanding of how language works.